Sediment composition mediates the invasibility of aquatic ecosystems by a non-native Poaceae species - Fasoli,José Vitor Botter (2015)
Aim: To test the invasibility of aquatic ecosystems by an exotic species, we used the invasive macrophyte Urochloa arrecta, which has invaded many Neotropical waterbodies and has reduced biodiversity in these habitats. The extensive growth of this macrophyte can be related to its affinity for mud-rich sediments, which occur primarily in secondary river channels and lentic habitats.MethodsTo test this hypothesis, we cultivated U. arrecta in trays with different percentages of mud and we measured the sprout length and biomass of the plants after 75 days.ResultsOur results showed a positive and significant relationship between sediment mud percentage and nitrogen, phosphorus and organic matter. Both plant length and biomass increased significantly and continuously with increasing mud content, indicating that the growth of this species is not limited even at the highest levels of mud, which is shown to be toxic for other species of macrophytes. Thus, it is probable that sand-rich sites, such as river shores, are less vulnerable to invasion by this species than relatively mud-rich sites, such as lakes.ConclusionsThis finding indicates that relatively mud-rich ecosystems should be prioritised in monitoring programs to prevent invasion by this species. In addition, the slow development of this species in sandy sediments opens a potential window for its management, at least on small spatial scales. However, despite the reduced growth of U. arrecta in sand-rich sediments, this grass is able to grow in several types of sediments, which explains its spread in a variety of habitats in Neotropical freshwater ecosystems.